2019 22nd Euromicro Conference on Digital System Design (DSD) 2019
DOI: 10.1109/dsd.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Domain Knowledge for the Efficient Design-Space Exploration of Advanced Cyber-Physical Systems

Abstract: Cyber-physical systems are becoming increasingly complex. In these advanced systems, the different engineering domains involved in the design process become more and more intertwined. In these situations, a traditional (sequential) design process becomes inefficient in finding good designs options. Instead, an integrated approach is needed where parameters in both the control and embedded domain can be chosen, evaluated and optimized to have a good solution in both domains. However, in such an approach, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…This synthesis is mainly based on the task the robot should fulfill and the results show that such a synthesis can outperform genetic algorithm optimizations. In the work of [11], the authors show how domain knowledge can be used to guide the designspace exploration process for an advanced control system and its deployment on embedded hardware. They choose this integrated approach because the parameters in both the control and embedded domain can be chosen, evaluated and optimized to have a performant solution in both domains although the combined design space becomes vast.…”
Section: A Cps Design Space Explorationmentioning
confidence: 99%
“…This synthesis is mainly based on the task the robot should fulfill and the results show that such a synthesis can outperform genetic algorithm optimizations. In the work of [11], the authors show how domain knowledge can be used to guide the designspace exploration process for an advanced control system and its deployment on embedded hardware. They choose this integrated approach because the parameters in both the control and embedded domain can be chosen, evaluated and optimized to have a performant solution in both domains although the combined design space becomes vast.…”
Section: A Cps Design Space Explorationmentioning
confidence: 99%
“…However, here the speed is directly imposed by the user and thus always known. Therefore, a current level feedforward controller can be designed that anticipates on speed variations based on G d2 (18), see Section VI. The process dynamics of the system are characterized by the location of the poles being the roots of the denominator of (16)(17)(18).…”
Section: A System Dynamicsmentioning
confidence: 99%
“…Measurements in [17] show an energy saving potential up to 9.5% when the BLDC motor is driven with sinusoidal instead of square-wave shaped currents. With a view to final implementation, the first steps have already been taken for the design-space exploration process for the proposed advanced control technique and its optimal deployment on embedded hardware [18]. However, one missing link still needs to be tackled to arrive at a deployable energy optimal control technology for BLDC motors.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [7], [8], we have already shown how domain knowledge, captured in an ontology, is used to solve multi-domain optimization problems. We showed that by building an ontology of important design parameters and their interdependencies, it becomes possible to reason about the design space exploration workflow and to subsequently determine an efficient one.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, we manually derived a DSE workflow for the same example case as in this paper [7]. We did this by first building a similar ontology of the system under design.…”
Section: Comparison To Manual Approachmentioning
confidence: 99%